LITERASI KEUANGAN PADA UMKM SP PLAZA, BATU AJI KOTA BATAM - Tiurniari Purba; Vargo Christian L. Tobing; Nora Pitri Nainggolan; Ronald Wangdra (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Financial literacy is the knowledge and confidence required to possess about financial services institutions and products, including features, benefits and risks, rights and obligations related to financial products and services, and skills in using them. Objective: In the Batu Aji area of ​​Batam City, many MSMEs have the potential to grow but still face challenges in managing their business finances. Therefore, educational and mentoring activities regarding financial literacy are needed to empower MSMEs to manage their business finances more effectively and professionally. Method: This community service activity was implemented using lectures and discussions. Results: This activity provided an understanding of the importance of utilizing digital technology in financial management. Several participants became interested in using a simple financial recording application on their mobile phones to assist with recording daily transactions. The use of digital technology is considered to help MSMEs become more orderly and efficient in managing their businesses. Conclusion: Overall, this community service activity had a positive impact on increasing the knowledge and awareness of MSMEs regarding the importance of financial literacy.